Decreased fibrinolytic activity in juvenile chronic arthritis. Issue 12 (December 1990) - Mussoni, L; Pintucci, G; Romano, G; De Benedetti, F; Massa, M; Martini, A
Abstract : The basal fibrinolytic activity in 17 children with active juvenile chronic arthritis (JCA) was investigated. It was found that patients with JCA, and particularly those with the systemic form, show decreased plasma fibrinolytic activity and a marked increase in plasminogen activator inhibitor. Additionally, it was found that patients with systemic JCA, but not those with the polyarticular or pauciarticular form, have increased circulating levels of tissue-type plasminogen activator, and endothelial cell protein, suggesting possible endothelial cell participation in systemic JCA.